Drivers of Health Insurance Coverage in Low Income Settlements: A Case of Kibera Informal Settlement, Nairobi County, Kenya - Ng’ang’a, Emmah Wanjiku; Odhiambo, Martine Oleche (European Scientific Journal, ESJ, 2023)
Insurance is critical for any country’s economic growth and development to be sustainable. In rural areas of Kenya, among the illiterate, unemployed, poor, and vulnerable in society, health insurance adoption is extremely low. This paper focuses on determining the drivers for health insurance uptake among low-income populations in Kibera, Nairobi County. Semi structured questionnaires were administered to households located in Kibera informal settlements to collect data. The Yamane (1967) formula was used to select the sample size. Simple random sampling was adopted in selecting 399 respondents. Both descriptive and inferential analysis were conducted. The binary probit regression model was employed. Health insurance ownership was used as the dependent variable while age, gender, marital status, household size, school attainment, occupation, income levels, religion, cultural beliefs, frequency of hospital visits, cost of premiums, and pre-existing illness were used as the independent variables. Findings revealed that only 27.6 percent of the respondents had health insurance coverage. The findings further revealed that occupation, income levels, and religion significantly influence health insurance ownership among low-income populations in Kibera, Nairobi. Public health insurance cover was the most owned type of health insurance scheme. Recommendations were highlighted for the ministry of health and other relevant stakeholders to raise knowledge on the various health insurance options available and improve flexibility of the products to drive insurance uptake. In addition, national and county governments need to develop programmes and policies that could empower households in the informal settlements. Further, it is necessary for the government to subsidise the cost of acquiring public health insurance covers since this would encourage uptake among low-income families. The ministry of health should also work in conjunction with various religious denominations to campaign for uptake of health insurance among the poor.